2022
DOI: 10.3389/fimmu.2022.858021
|View full text |Cite
|
Sign up to set email alerts
|

Anti-PD-1 Therapy Enhances the Efficacy of CD30-Directed Chimeric Antigen Receptor T Cell Therapy in Patients With Relapsed/Refractory CD30+ Lymphoma

Abstract: Anti-CD30 CAR-T is a potent candidate therapy for relapsed/refractory (r/r) CD30+ lymphomas with therapy limitations, and the efficacy needed to be further improved. Herein a multi-center phase II clinical trial (NCT03196830) of anti-CD30 CAR-T treatment combined with PD-1 inhibitor in r/r CD30+ lymphoma was conducted. After a lymphocyte-depleting chemotherapy with fludarabine and cyclophosphamide, 4 patients in cohort 1 and 3 patients in cohort 2 received 106/kg and 107/kg CAR-T cells, respectively, and 5 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Therefore, the immune checkpoint blocker PD-1 mAb is the most widely used reagent for anti-tumor immunotherapy in clinical practice [28][29][30]. However, prior to performing the PD-1 mAb therapy, positive detection of PD-1 is necessary [31,32]. Moreover, numerous studies have suggested that the number of T cells in the tumor tissue directly affects the outcome of the PD-1 mAb anti-tumor immunotherapy [33,34], implicating that the existence of T cells is essential for anti-tumor immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the immune checkpoint blocker PD-1 mAb is the most widely used reagent for anti-tumor immunotherapy in clinical practice [28][29][30]. However, prior to performing the PD-1 mAb therapy, positive detection of PD-1 is necessary [31,32]. Moreover, numerous studies have suggested that the number of T cells in the tumor tissue directly affects the outcome of the PD-1 mAb anti-tumor immunotherapy [33,34], implicating that the existence of T cells is essential for anti-tumor immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with Malignant Pleural Disease in a Phase I Trial of CAR T-cell combination with Pembrolizumab, have a median overall survival of 23.9 months ( 211 ). In another multi-center phase II trial, the combination of anti-PD-1 antibody enhanced CAR-T therapy in lymphoma patients with minimal toxicities ( 212 ).…”
Section: Combination Therapymentioning
confidence: 99%
“…Combination with an anti-PD1 Ab, therefore, appeared to reinforce the action of anti-CD30 CAR-T cells and was very well tolerated. 70 A 21-year-old woman with scleronodular HL, initially treated by standard ABVD-based chemotherapy, was treated by anti-CD19 and anti-CD30 CAR-T cells after myeloablaive chemotherapy 10 months later. The patient received three administrations of anti-CD19 CAR-T cells (1.61, 5.20 and 5.20 × 10 5 cells/kg).…”
Section: Cell and Gene Therapiesmentioning
confidence: 99%